Digital Health Technologies And Their Application In Improving Pediatric Healthcare Delivery Systems - Rehman H, Dr. Ubaidur; P, Dr. Mohanraj; K S, Sridevi Sangeetha; P, Prakash (Adolescência e Saúde, 2026)
Background: Digital health technologies such as telemedicine, mobile health applications, electronic health records are rapidly changing the delivery of pediatric healthcare improving access, efficiency, and quality of care. Objective: This paper will explore the use and viability of digital health technologies in enhancing the delivery of healthcare services to the pediatric system. Methodology: The mixed-method was implemented, where 40 peer-reviewed sources published in 2018-2024 were analyzed as part of the systematic review, and information on surveys of 120 professionals working in the pediatric care setting were compiled. Findings: Findings show that digital health programs enhanced healthcare access by 35 per cent among rural communities and decreased hospital readmission rates by 20 per cent. Telemedicine platforms improved patient-follow-up and monitoring, whereas mobile health applications aided in the earlier diagnosis and parental involvement. However, issues of privacy of the data, low level of digital literacy and constant lack of infrastructure were found. Conclusion: Digital health technologies have a huge potential to support the provision of healthcare to pediatrics by enhancing the level of access, efficiency, and patient outcomes. The solutions to the implementation barriers and equitable access will be necessary to maximize their benefits in the pediatric healthcare systems.